Evidence for unique DNA repair activity encoded by a cloned Serratia marcescens gene: suppression of Escherichia coli mutations that reduce repair of alkylated DNA. - Murphy, K E (1989)
A recombinant plasmid containing a Serratia marcescens DNA repair gene has been analyzed biochemically and genetically in Escherichia coli mutants deficient for repair of alkylated DNA. The cloned gene suppressed sensitivity to methyl methanesulfonate of an E. coli strain deficient in 3-methyladenine DNA glycosylases I and II (i.e., E. coli tag alkA) and two different E. coli recA mutants. Attempts to suppress the methyl methanesulfonate sensitivity of the E. coli recA mutant by using the cloned E. coli tag and alkA genes were not successful. Southern blot analysis did not reveal any homology between the S. marcescens gene and various known E. coli DNA repair genes. Biochemical analysis with the S. marcescens gene showed that the encoded DNA repair protein liberated 3-methyladenine from alkylated DNA, indicating that the DNA repair molecular is an S. marcescens 3-methyladenine DNA glycosylase. The ability to suppress both types of E. coli DNA repair mutations, however, suggests that the S. marcescens gene is a unique bacterial DNA repair gene.